The Shaping Power of Monstrosity and Grotsquery in the Post-Apocalyptic Setting of Jeff VanderMeer’s Borne and Dead Astronauts - Indrajit Patra (Selected Topics in Humanities and Social Sciences Vol. 1, 2021)
The study seeks to analyze Jeff VanderMeer’s ‘Borne’ and ‘Dead Astronauts’ to describe how the shaping power of monstrosity, weirdness, complexity, and grotesquery in a post-apocalyptic setting can best be appreciated once one applies certain religious tropes for the analysis of the unfolding of the events in the novel. In post-apocalyptic settings of the novels mentioned above, Biblical tropes can help connect the present situation to a past that otherwise exists as a dead and desolate wasteland devoid of any meaning. For the purpose of formulating the theoretical framework, the study employs Foucault’s and Negri’s ideas of monstrosity and Bakhtin’s idea of grotesque as its mainstay.